Evaluation of chemotherapy treatments used in colorectal cancer therapy: A narrative review (Research, Society and Development, 2022)
Colorectal cancer is the fourth neoplasm in number of deaths in the world. It affects thousands of people, often diagnosed at a late stage, making a cure impossible. Therefore, we seek to adapt the treatments already known, as well as to develop new forms of therapies. The objective of this research was to find recent studies that sought to evaluate the different therapies used for colorectal cancer. Methodology: A bibliographic review was carried out, where the articles searched were searched in the Pubmed database, using keywords. Results: Twenty articles were analyzed for the construction of the review. Conclusion: Among the studies found by this review, it is clear that some have very encouraging results in relation to new treatments for colorectal cancer, but they need further research, increasing, for example, the number of participants. The biggest problem about the treatment of intestinal cancer is still the late diagnosis and the toxicity/safety of the therapies used, and some studies have stopped to research them, trying to find ways to reduce the side effects in the patient, improving their well-being.